Faktor Risiko Stunting pada anak di Negara Berkembang - Indah Budiastutik (Amerta Nutrition, 2019)
Background: The problem of stunting occurs in developing countries including Indonesia. In Indonesia the prevalence of child stunting is 30.8%, still above the world prevalence, which is 22.2%. The prevalence of stunting in sub-Saharan Africa is 34.5%, in Ethiopia is 52.4%, and the prevalence of stunting in Congo is 40%. While WHO stipulates that nutrition problems should not exceed 20%. Stunting could inhibit linear growth, development and degenerative diseases later in adulthood.